PECULIARITIES OF BUSINESS DEVELOPMENT IN THE CONTEXT OF DIGITALIZATION OF THE ECONOMY - Liudmyla Kysh (Izdevnieciba "Baltija Publishing", 2022)
Today it is very important to determine the key positions of industrial enterprises in these areas to form strategic trajectories of business development, successful innovation activities of which determine economic growth and prosperity of the global economy. It is strategic management that allows modern enterprises and organizations not only to ensure the desired result with the digitalization of all business processes, but also to lay the foundation for innovative development, ensuring a high level of competitiveness of the global economy. Digitalization is one of the main factors of economic growth and business competitiveness. The use of digital technology enables companies in all sectors of the economy to grow faster, better and more efficiently. This is of great interest within the concept of digital economy and digitalization. The purpose of this study was to identify ways to overcome the obstacles and problems caused by digitalization in the activities of enterprises. The purpose of this study is to analyze the impact of digitalization on enterprises and scientifically justify strategies to overcome the challenges and obstacles to development. This goal necessitated a number of tasks: to analyze the documents issued by international professional organizations; to identify the advantages and disadvantages of digitalization from the perspective of enterprises; to substantiate strategic directions to overcome obstacles to the digitalization of the enterprise. The methodology of the study is based on the use of such methods and techniques of scientific knowledge as analysis, synthesis, description and comparison. The application of the methods made it possible to highlight the advantages and disadvantages of the impact of digitalization on the activities of enterprises. At the same time, the article identifies the main strategic trajectories of enterprise development in the digitalization of the economy. It is proved that the digitalization of the economy leads to the transformation of traditional production processes and is interconnected with technological innovations and organizational changes, modifies the corporate culture of any industrial enterprise. Digital transformation affects not only the production sphere of companies, but also the entire system of business organization and operation. All processes related to the production of a company's products are changing: some of them are being algorithmized, reducing the transaction costs of the company.